ANALISIS KESALAHAN FONETIK MAHARAH QIRAAH PADA MAHASISWA - Firdaus, M (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
This study aims to identify the phonetic errors of Perbankan Islam students at IAIN Takengon in reading Arabic texts. It is highly recommended that these phonetic errors are not continuously made in the future and hence the phonetic errors made by students must be analyzed to find problems and eventually come up with appropriate learning methods. This study used descriptive qualitative methods and the data in this study were obtained through interview and observation techniques. Interviews and observations were carried out on 26 active students of Islamic Banking IAIN Takengon utilizing free reading, listening, taking notes, and recording their readings to gain insight into their phonetic errors. was concluded that there had been a phonetic error made by the students in the pronunciation of the following letters “ع” (‘ain) resembles “ء” (hamzah) 80,76%; “ض” (ḍad) resembles “ظ” (ẓa), “د” (dal) or “ج” (jim) 84,61%; “ش” (syin) resembles “س” (sin) 38,46%; “ث” (ṡa) resembles “س” (sin) 69,23%; “هـ” (ha) resembles “ح” (ḥa) 23,07%; “ق” (qaf) resembles “ك” (kaf) 34,61%; “ز” (zai) resembles “ج” (jim) 57,69%; “ذ” (żal) resembles “د” (dal) and “ز” (zai) 50%; “ص” (ṣad) resembles “س” (sīn) 50%; “ح” (ḥa) resembles “هـ” (ha) 15,38%; “خ” (kha) resembles “ح” (ḥa) and “غ” (ga) 57,69%; “ط” (ṭa) resembles “ت” (ta) and “د” (dal) 34,61%; and “ظ” (ẓa) resembles “ز” (zai), “ج” (jim), “د” (dal) dan “ذ” (żal) 65,38%.